2010
DOI: 10.1073/pnas.1009320107
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive microRNA expression profiling of the hematopoietic hierarchy

Abstract: The hematopoietic system produces a large number of highly specialized cell types that are derived through a hierarchical differentiation process from a common stem cell population. miRNAs are critical players in orchestrating this differentiation. Here, we report the development and application of a high-throughput microfluidic real-time quantitative PCR (RT-qPCR) approach for generating global miRNA profiles for 27 phenotypically distinct cell populations isolated from normal adult mouse hematopoietic tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
138
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(146 citation statements)
references
References 30 publications
7
138
0
1
Order By: Relevance
“…S1C). A previously published data set confirmed this expression pattern in murine cells (Petriv et al 2010).…”
Section: Resultssupporting
confidence: 74%
“…S1C). A previously published data set confirmed this expression pattern in murine cells (Petriv et al 2010).…”
Section: Resultssupporting
confidence: 74%
“…The most comprehensive analysis implicating miRNAs in hematopoiesis showed that certain miRNAs are distinctly expressed in mouse hematopoietic sub-populations. 15 This finding is supported by Dicerdeficient mice, which are unable to process any mature miRNA. The Dicer-deficient mice are depleted of HSC, 16 exhibit developmental defects in pro-B cells, 17 as well as impaired T-cell differentiation and cytokine production.…”
Section: Overview Of Mirnas In Regulating Hematopoiesissupporting
confidence: 60%
“…8 Also, cell-to-cell expression is often heterogeneous, requiring large-scale analysis for the quantification of multiple miRNA expressions at the single-cell level. To translate to a single assay, one often relies on sequence-dependent target amplification via RT-PCR, 31,32 which potentially requires probe-set modification that may be difficult to scale-up. Instead, our versatile system is capable of incorporating a signal-based amplification scheme 23,33−35 such as rolling circle amplification (RCA) without a need for extensive optimization regardless of cell type or miRNA target.…”
mentioning
confidence: 99%